The effectiveness of correction of multistage wattmeters additive error - Ларин, Виталий Юрьевич; Синицкий, Олег Павлович; Щербань, Анастасия Павловна (Technology audit and production reserves, 2014)
The dependences for the suppression ratios of additive noise of two-, three- and four-stage integrating wattmeters, taking into account the integration efficiency and low and high frequencies influence were considered in the paper. The effect of input variable phase with respect to noise was defined. It is shown that at the alternating noise spectrum, dispersion in readings, caused by the additive error influence at four-stage operation mode will be greater than for instruments, operating at fewer stages. It was determined that the constant drift component is not included in the readings at the four-stage operation mode. It was revealed that for the low-frequency components of the noise signal, the suppression ratio largely depends on the integration time and the noise signal phase. The research results, described in the paper can be applied in the designing high-precision multistage digital wattmeters, in the operation conditions of enterprises, which use secondary switched-mode power supplies for equipment and instruments operation, as well as in the practice of metrological services when performing electrical measuring instruments verification.